Correlation between anxiety and critical reading ability of Indonesian English as a Foreign Language students - Fitrawati Fitrawati; Erdiana Erdiansyah; David D. Perrodin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study investigates the possible relationship between reading anxiety and the critical reading ability of tertiary EFL students majoring in English education at a state university in West Sumatra, Indonesia. Thirty-two students were selected utilizing convenience sampling as the research sample. By employing a correlational approach, the instrument used for this analysis was a TOEFL test consisting of 30 questions to measure students' ability to read critically. In addition, a questionnaire was also developed based on the theory of experts composed of 20 statements used to measure students' reading anxiety. Pearson product-moment correlation was used to investigate the relationship between reading anxiety and students' critical reading ability. The study found that 1) most students experience anxiety at the intermediate level, 2) the level of students' critical reading ability is at the average level, and 3) there is a significant relationship between students' reading anxiety and critical reading ability. The results imply that the reading anxiety students experience correlates to their scores in critical reading, leading to a significant effect of reading anxiety on students' critical reading skills.